1984
DOI: 10.1071/ph840179
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Vertical Vorticity on Thermal Convection

Abstract: The single-mode equations of Boussinesq thermal convection have been modified to include the vertical component of vorticity, which has led, in certain parameter ranges, to a new family of solutions for stationary convection in the absence of external constraints. The features of these solutions are discussed and a comparison with the family of solutions possessing zero vertical vorticity, which are also solutions of the equations, is presented. Specifically, these new solutions are characterized by a lower ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…The two bifurcating states are reflection-symmetry related. This is a well-known way to generate swirl via symmetry breaking, already observed in convection problems (Murphy & Lopez 1984;Massaguer, Mercader & Net 1990), and recently in localized heating in a cylindrical annulus (Navarro & Herrero 2011). In the present problem there is no swirl generation in the first bifurcation.…”
Section: Symmetriesmentioning
confidence: 64%
“…The two bifurcating states are reflection-symmetry related. This is a well-known way to generate swirl via symmetry breaking, already observed in convection problems (Murphy & Lopez 1984;Massaguer, Mercader & Net 1990), and recently in localized heating in a cylindrical annulus (Navarro & Herrero 2011). In the present problem there is no swirl generation in the first bifurcation.…”
Section: Symmetriesmentioning
confidence: 64%
“…Nevertheless, it is still felt that the fluid will endeavour to transport heat in the most efficient manner, but it will also select the most stable mode which is compatible with efficiency. Murphy and Lopez (1984) demonstrated the existence of a new state which, although being less efficient than the usual state determined by the steady single-mode system of equations with hexagonal planform, has a number of properties rendering it the more stable of the two, and hence probably the preferred state. Murphy and Lopez (1984) made a detailed examination of this new state, concentrating on the effects of varying the Rayleigh and Prandtl numbers, with a fixed value of the horizontal wave number, on the steady state system.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical investigations often either employ linearized Atmospheric Science Letters (2001Letters ( ) doi:10.1006Letters ( /asle.2001 1530-261X * c 2001 Royal Meteorological Society equations or a truncated nonlinear expansion, and generally do not present vertical vortices as solutions. One notable exception is Murphy and Lopez (1984) and Lopez and Murphy (1984), whose studies with a nonlinear``single-mode approximation'' revealed an onset of rotation in convection which had no Coriolis force or other vertical torques. A laboratory simulation of Rayleigh±Be Ânard convection in which vertical vortices were documented was carried out by Willis and Deardorff (1979).…”
Section: Introductionmentioning
confidence: 99%